Endometriosis of the anterior abdominal wall: ultrasound imaging data - E. V. Komlichenko (Акушерство, гинекология и репродукция, 2021)
Endometriosis of the anterior abdominal wall is a rare disease comprising 0.3–3.5 %. In turn, its diagnosis is quite challenging due to the nonspecific picture, including pain in the anterior abdominal wall during menstruation. Upon clinical examination, a thickened area may be observed in the anterior abdominal wall, usually in the area of tissue involved in surgery. Ultrasound examination is a simple, economical, and reliable method of choice to diagnose extragenital endometriosis. Here we describe a case report of the patient after surgery of anterior abdominal endometriosis localized in the rectus abdominis muscle in the umbilical region and confirmed by ultrasound test and morphological examination of excised macroscopic sample.